(untitled) (Alberta Journal of Educational Research, 2016)
Teachers’ job satisfaction leads to job continuity, which in turn affects teacher performance as well as the effectiveness of their institutions. The purpose of this study was to identify if there was a relationship between the Organizational Citizenship Behavior (OCB) and Job Satisfaction (JS) of teachers since discretionary behaviours have a significant impact on performances, yet are not considered in evaluations. Descriptive correlational research was carried out using a multi-stage stratified random sampling technique, where participants came from Higher Education Commission (HEC) recognized public and private sector universities in Lahore, Pakistan. After data cleaning, statistical analyses were applied to the data from 232 questionnaires, using SPSS. Correlations between the factors of organizational citizenship behaviour (altruism, courtesy, sportsmanship, conscientiousness, and civil virtue) and job satisfaction were found to be moderately significantly positive. Job satisfaction through the factors of OCB was determined to be 21.3%, where only altruism and civil virtue were factors. Significant differences were revealed in the OCB and job satisfaction of university teachers in terms of gender, university type, job type, marital status, age groups, academic qualifications, teaching experiences, faculties, and universities. Results of the study provide implications for educational administrators, teachers, and policy makers for incorporating OCBs in their organizations and strengthening factors that contribute toward job satisfaction. La satisfaction professionnelle chez les enseignants entraine la continuité au travail, ce qui affecte le rendement des enseignants et l’efficacité de leurs établissements d’enseignement. L’objectif de cette étude était d’établir s’il existe un lien entre la citoyenneté organisationnelle (CO) et la satisfaction professionnelle (SF) des enseignants car, même si le comportement discrétionnaire a un impact significatif sur le rendement, les évaluations n’en tiennent pas compte. Une recherche descriptive corrélationnelle basée sur une méthodologie d’échantillonnage aléatoire stratifié à plusieurs degrés a impliqué des participants d’universités publiques et privées reconnues par le Conseil de l’enseignement supérieur à Lahore, au Pakistan. Suivant un nettoyage des données, nous avons soumis les données provenant de 232 questionnaires à des analyses statistiques avec le logiciel SPSS. Des corrélations légèrement positives se sont révélées entre les caractéristiques de la citoyenneté organisationnelle (altruisme, courtoisie, esprit sportif, conscience professionnelle, sens civique) et la satisfaction professionnelle. La satisfaction professionnelle, telle qu’évaluée par les caractéristiques de la CO, était de 21,3% et seulement l’altruisme et le sens civique y jouaient un rôle. Les résultats ont révélé des différences significatives quant à la CO et la satisfaction professionnelle chez les professeurs d’université en ce qui concerne les sexes, le type d’université, le type d’emploi, le statut civil, les groupes d’âge, les titres universitaires, l’expérience en enseignement, les facultés et les universités. Ces résultats ont des implications susceptibles d’intéresser les administrateurs, les enseignants et les décideurs par rapport à l’intégration de la CO au sein de leur établissement et au renforcement des facteurs qui contribuent à la satisfaction professionnelle.